Behcet disease: Neurological and psychiatric manifestations observed in two patients in the Dos de Mayo Nation al Hospital (Lima, Peru). - Castañeda, Marco A. (2022)
The neurological and psychiatric manifestations in two patients who met clinical criteria of Behcet’s disease are observed and described throughout several decades. The presence of recurrent oral and genital canker sores is illustrated with images. One of the patients developed thrombosis of the femoral vein, and erythema nodosus was present in both. The ophthalmological evaluation showed absence of uveitis in both patients, and blindness by adult monocular dystrophic maculopathy without signs of retinal vasculitis in the female. Laboratory tests on blood and cerebrospinal fluid evidenced lymphocytic pleocytosis. The patergia skin test was negative. Likewise, laboratory tests determined an absence of findings compatible with other autoimmune diseases. Throughout the evaluation period, the clinical manifestations were correlated with the findings from tomography and brain magnetic resonance magnetic. Similarly, recurrent myelitis and its correlation with the results of medular magnetic resonance imaging are explained. The evaluation and follow-up period through outpatient consultation and hospitalization was prolonged: the 73-year-old male patient, who started the disease at age 35, was followed-up for 34 years; and the 50-year-old female patient, fell ill at the age of 28 and was followed-up for 8 years. This process allowed the understanding of the different morbid factors that influenced the serious evolution of the clinical picture.